2023
DOI: 10.1186/s40364-023-00506-4
|View full text |Cite
|
Sign up to set email alerts
|

SYT7 regulates the progression of chronic lymphocytic leukemia through interacting and regulating KNTC1

Abstract: Background Chronic lymphocytic leukemia (CLL) is one of the most frequent occurring types of leukemia. It typically occurs in elderly patients and has a highly variable clinical course. At present, the molecular mechanism driving the pathogenesis and progression of CLL is not fully understood. The protein Synaptotagmin 7 (SYT7) encoded by the SYT7 gene has been found to be closely related to the development of various solid tumors, but its role in CLL is unclear. In this study, we investigated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Ubiquitination modification has long been an area of keen interest for researchers, especially in the field of protein regulation ( Wang et al, 2022 ; Zhang et al, 2023b ). The discovery that ubiquitination targets proteins for proteasomal degradation earned the Nobel Prize in Chemistry in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Ubiquitination modification has long been an area of keen interest for researchers, especially in the field of protein regulation ( Wang et al, 2022 ; Zhang et al, 2023b ). The discovery that ubiquitination targets proteins for proteasomal degradation earned the Nobel Prize in Chemistry in 2004.…”
Section: Discussionmentioning
confidence: 99%
“…Functional enrichment analysis revealed that Kntc1 was mainly associated with autophagosome and pyrimidine metabolism. Recent studies have suggested that mitogenic proteins may be potential biomarkers and may contribute to the development of human malignancies 20 . It has been frequently associated with tumors of the digestive and genitourinary systems 21 .…”
Section: Discussionmentioning
confidence: 99%
“…Emerging clinical findings have indicated that high levels of SYT7 expression are correlated with the progression and worsened outcomes of patients [ [4] , [5] , [6] ]. Laboratory studies have shown that suppressing SYT7 may reduce the malignancy of lymphocytic leukemia and colorectal cancer [ 7 , 8 ], suggesting its role as a cancer-promoting factor. Nonetheless, the SYT7-mediated regulation of CC has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%